An Illusory Consensus behind GMO Health Assessment. (November 2015) - Krimsky, Sheldon
Prominent scientists and policymakers assert with confidence that there is no scientific controversy over the health effects of genetically modified organisms (GMOs)—that genetically modified crops currently in commercial use and those yet to be commercialized are inherently safe for human consumption and do not have to be tested. Those who disagree are cast as "GMO deniers." This article examines scientific reviews and papers on GMOs, compares the findings of professional societies, and discusses the treatment of scientists who have reported adverse effects in animal feeding experiments. This article concludes by exploring the role that politics and corporate interests have had in distorting an honest inquiry into the health effects of GMO crops.